Evaluation of the Efficacy of 3D-Printed Customized Orthodontic Brackets in Reducing Treatment Time and Improving Outcomes - Mohammad K. Alam; Mohammad Y. Hajeer; Abdullah H. Alshammari; Zeyad M. M. Alenezi; Shouq B. Aldhafeeri (Journal of Pharmacy and Bioallied Sciences)
Background: The advent of 3D printing technology has revolutionized orthodontic treatment, enabling the production of customized orthodontic brackets tailored to individual patients. These customized brackets are hypothesized to reduce treatment time and improve clinical outcomes by providing better alignment precision and minimizing the need for adjustments. Materials and Methods: A randomized controlled trial was conducted with 60 patients aged 12–25 years requiring orthodontic treatment. The participants were randomly assigned to two groups: the experimental group (n = 30) received 3D-printed customized orthodontic brackets, while the control group (n = 30) received conventional brackets. Treatment duration, the number of adjustment visits, and the quality of alignment were recorded over an 18-month period. Quality of alignment was assessed using the American Board of Orthodontics (ABO) grading system. Statistical analysis was performed using a paired t-test to compare the outcomes between the two groups. Results: The average treatment time for the experimental group was significantly shorter, with a mean duration of 14.2 months (SD ± 1.8) compared to 18.6 months (SD ± 2.3) in the control group (P < 0.01). The number of adjustment visits was reduced by 35% in the experimental group (mean = 8 visits) compared to the control group (mean = 12 visits). Furthermore, the quality of alignment, as measured by the ABO grading system, was significantly higher in the experimental group (mean score = 90.5) compared to the control group (mean score = 78.2) (P < 0.05). Conclusion: The use of 3D-printed customized orthodontic brackets significantly reduces treatment time and improves the quality of orthodontic outcomes compared to conventional brackets. These findings suggest that customized brackets offer a promising approach for enhancing the efficiency and effectiveness of orthodontic treatment, potentially leading to better patient satisfaction and reduced clinical workload.